1989
DOI: 10.1002/jlb.45.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Expression of Activation Markers on Human Peripheral Blood Mononuclear Cells by In Vitro Culture With Retinoids and Carotenoids

Abstract: Retinoids (retinol, retinal, retinoic acid, retinyl beta-glucuronide, and 13-cis retinoic acid) and carotenoids (beta-carotene and canthaxanthin) were evaluated for their immunomodulatory effects on human peripheral blood T-lymphocyte subpopulations and natural killer (NK) cells. Peripheral blood mononuclear cells (PBMC) from healthy young volunteers were isolated and incubated for 72 hours at various levels of retinoids and carotenoids including a physiological concentration (10(-8) M). Expression of surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(20 citation statements)
references
References 16 publications
5
15
0
Order By: Relevance
“…Vegetarians, whose vitamin A, vitamin E and vitamin C serum levels were equivalent to non-vegetarians, but whose @-carotene serum levels were twice as high as non-vegetarians, had twice the natural killer cell activity as the non-vegetarians (Malter et al 1989). Peripheral leucocyte cells from eleven adults, when cultured with 1 nM-@-carotene or 1nM-canthaxanthin for 72 h showed enhanced levels of cell surface markers indicative of natural killer cells, such as increases in surface markers for human leukocyte antigen-Dr, transferrin and interleukin 2 receptor (Prabhala et al 1989). Similar enhancement in these markers was also seen when elderly individuals were given @-carotene (30 mg/d for 2 months) (Watson et al 1991).…”
Section: Macrophage Functionssupporting
confidence: 52%
“…Vegetarians, whose vitamin A, vitamin E and vitamin C serum levels were equivalent to non-vegetarians, but whose @-carotene serum levels were twice as high as non-vegetarians, had twice the natural killer cell activity as the non-vegetarians (Malter et al 1989). Peripheral leucocyte cells from eleven adults, when cultured with 1 nM-@-carotene or 1nM-canthaxanthin for 72 h showed enhanced levels of cell surface markers indicative of natural killer cells, such as increases in surface markers for human leukocyte antigen-Dr, transferrin and interleukin 2 receptor (Prabhala et al 1989). Similar enhancement in these markers was also seen when elderly individuals were given @-carotene (30 mg/d for 2 months) (Watson et al 1991).…”
Section: Macrophage Functionssupporting
confidence: 52%
“…On the other hand, incubation with 10 5 -10 7 M retinoic acid increased two-fold human natural killer (NK) cell activity [29] while it stimulated 20-fold the mouse cytotoxic T-cells activity [12]. A possible explanation for these results could be the finding that plasma membrane alterations and high surface receptor expression can be induced in human cytotoxic cells in vitro by retinoic acid [30,32].…”
Section: Discussionmentioning
confidence: 97%
“…They attributed this stimulatory effect to a direct carotenoid effect of p-carotene since canthaxanthin cannot be converted to vita min A. Other evidence for a specific role played by P-carotene have been provided by Prabhala et al [32] who showed that P-caro tene and canthaxanthin dramatically in creased natural killer cell population of hu man peripheral blood mononuclear cells and also produced a small increase in T-helper cells. In an earlier study, Alexander et al [ 14] similarly reported increased OKT4+ helper cells in human orally supplemented with Pcarotene.…”
mentioning
confidence: 82%